GAMBARAN STATUS GIZI MENGGUNAKAN KMS REMAJA PADA SANTRI PUTRI DI SMA UNGGULAN HAF-SA ZAINUL HASAN BPPT GENGGONG KABUPATEN PROBOLINGGO - Meiriyantika, Maulida Khofifah; Mansur, Herawati; Rosmalawati, Ni Wayan Dwi (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2024)
Abstract: The health status of adolescents is an important thing that must be considered. The teenage period is one of the stages of a person's life where weight and height growth peaks. This research aims to determine the description of nutritional status using KMS for young women at the leading high school Haf-Sa Zainul Hasan BPPT Genggong. This study aims to determine the description of nutritional status using KMS adolescents for female students at Unggulan Haf-Sa Zainul Hasan BPPT Genggong High School. The design in this research is descriptive quantitative. The population in this study were female students of Class XI and XII SMA Unggulan Haf-Sa Zainul Hasan BPPT Genggong, totaling 104 students. The sample was taken using proportional random sampling technique, totaling 51 respondents. The data collection tool measures nutritional status through weight and height which is plotted on the KMS chart for adolescents. Data analysis used descriptive analysis. The results of this study showed that most (54.90%) had more nutritional status and almost half (45.10%) had good nutritional status. Based on the results of research on the nutritional status of female students, the more dominant nutritional status. It is hoped that schools and health centers will hold socialization regarding general guidelines recommends consuming food according to "Fill My Plate" to fulfill balanced nutrition. The composition of "My Plate" consists of 1/3 portion of staple food, 1/3 portion of vegetables, and 1/3 portion of side dishes and fruits.Abstrak: Status kesehatan pada remaja menjadi hal penting yang harus diperhatikan. Periode remaja menjadi salah satu tahapan kehidupan seseorang dimana pertumbuhan berat badan dan tinggi badan mengalami puncaknya. Penelitian ini bertujuan untuk mengetahui Gambaran Status Gizi Menggunakan KMS Remaja Pada Santri Putri di SMA Unggulan Haf-Sa Zainul Hasan BPPT Genggong. Desain pada penelitian ini adalah deskriptif kuantitatif. Populasi dalam penelitian ini yaitu Santri Putri Kelas XI dan XII SMA Unggulan Haf-Sa Zainul Hasan BPPT Genggong sebanyak 104 santri dengan pengambilan sampel dengan teknik proportional random sampling berjumlah 51 responden. Alat pengumpulan data dengan grafik KMS remaja yaitu mengukur status gizi melalui BB dan TB. Analisis data menggunakan analisis deskriptif. Hasil pada penelitian ini, menunjukkan bahwa sebagian besar (54.90%) memiliki status gizi lebih dan hampir setengahnya(45.10%) memiliki status gizi baik. Berdasarkan hasil penelitian status gizi pada santri putri yang lebih dominan adalah status gizi lebih. Diharapkan untuk pihak sekolah dan puskesmas untuk mengadakan sosialisasi mengenai konsumsi makanan sesuai “Isi Piringku” untuk memenuhi gizi seimbang. Komposisi “Isi Piringku” terdiri dari makanan pokok 1/3 porsi, sayuran 1/3 porsi, dan lauk-pauk dan buah-buahan 1/3 porsi.